Comparison of euploidy rates of blastocysts in women treated with progestins or GnRH antagonist to prevent the luteinizing hormone surge during ovarian stimulation. Issue 6 (12th May 2020) - La Marca, Antonio; Capuzzo, Martina; Sacchi, Sandro; Imbrogno, Maria Giovanna; Spinella, Francesca; Varricchio, Maria Teresa; Minasi, Maria Giulia; Greco, Pierfrancesco; Fiorentino, Francesco; Greco, Ermanno
Abstract: STUDY QUESTION: Does the prevalence of euploid blastocysts differ between patients treated with progestin primed ovarian stimulation (PPOS) and those treated with conventional ovarian stimulation? SUMMARY ANSWER: The numbers of blastocysts and euploid blastocysts per patient and the number of euploid embryos per injected oocyte are similar for patients undergoing progestin-primed ovarian stimulation and for those undergoing conventional ovarian stimulation with GnRH antagonist. WHAT IS KNOWN ALREADY: New approaches to ovarian stimulation have been developed based on the use of drugs administrable by mouth instead of via injections. Attention has been dedicated to progestins to block the LH surge. Previous data regarding the number of oocytes retrieved and the number of good-quality embryos generated in PPOS have demonstrated similar outcomes when compared to conventional ovarian stimulation, even if some concerns regarding the quality of embryos have been advanced. STUDY DESIGN, SIZE, DURATION: This is a prospective non-inferiority age-matched case–control study. In a period of 6 months, a total of 785 blastocysts from 1867 injected oocytes obtained from 192 patients were available for analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: Infertile women undergoing IVF and preimplanation genetic testing (PGT) cycles were included. Forty-eight patients were treated with PPOS, and for each of them three age-matched historical controls ( n = 144) treated with a GnRH antagonist protocol were selected. PGT was performed according to next-generation sequencing technology. MAIN RESULTS AND THE ROLE OF CHANCE: Basal characteristics were similar in the two groups; a substantial similarity of the main outcome measures in the two treatment groups has also been found. The rate of formation of euploid blastocysts per oocyte was 21% in both the two treatment groups. The percentage of patients with euploid embryos and the total number of euploid blastocysts per patient (median and interquartile range, IQR) in the PPOS group were 38.7 (25.5–52.9) and 2 (1.3–3.1), respectively. These figures were not significantly different in women treated with the GnRH antagonist protocol i.e. 42 (28–53.8) and 2.1 (1.3–2.9), respectively. LIMITATIONS, REASONS FOR CAUTION: This was a case–control study which may limit the reliability of the main findings. WIDER IMPLICATIONS OF THE FINDINGS: Our results encourage the use of PPOS, especially for oocyte donation, for fertility preservation and for patients in which total freezing of embryos is foreseen, for those expected to be high responders or candidates for preimplantation genetic testing. However, studies aiming to investigate the effect of PPOS on the live birth rate are warranted. STUDY FUNDING/COMPETING INTEREST(S): None.